Hidden Markets: UI Design for a P2P Backup Application - Seuken, Sven; Jain, Kamal; Tan, Desney; Czerwinski, Mary (ACM Conference on Computer-Human Interaction, 2010)
The Internet has allowed market-based systems to become increasingly pervasive. In this paper we explore the role of user interface (UI) design for these markets. Different UIs induce different mental models which in turn determine how users understand and interact with a market. Thus, the intersection of UI design and economics is a novel and important research area. We make three contributions at this intersection. First, we present a novel design paradigm which we call hidden markets. The primary goal of hidden markets is to hide as much of the market complexities as possible. Second, we explore this new design paradigm using one particular example: a P2P backup application. We explain the market underlying this system and provide a detailed description of the new UI we developed. Third, we present results from a formative usability study. Our findings indicate that a number of users could benefit from a market-based P2P backup system. Most users intuitively understood the give & take principle as well as the bundle constraints of the market. However, the pricing aspect was difficult to discover/understand for many users and thus needs further investigation. Overall, the results are encouraging and show promise for the hidden market paradigm.